2010
DOI: 10.1128/jb.01165-09
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of the Three TATA Binding Protein Homologs in Methanosarcina acetivorans

Abstract: The roles of three TATA binding protein (TBP) homologs (TBP1, TBP2, and TBP3) in the archaeon Methanosarcina acetivorans were investigated by using genetic and molecular approaches. Although tbp2 and tbp3 deletion mutants were readily obtained, a tbp1 mutant was not obtained, and the growth of a conditional tbp1 expression strain was tetracycline dependent, indicating that TBP1 is essential. Transcripts of tbp1 were 20-fold more abundant than transcripts of tbp2 and 100-to 200-fold more abundant than transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 41 publications
2
13
0
Order By: Relevance
“…Our data is consistent with a previous study showing that the primary TATA binding protein (TBP; tbp1 ) transcript was similarly expressed under the three growth conditions [75]; however, it differs for comparisons of accessory TBPs wherein our data suggest that tbp2 and tbp3 are expressed at similar levels to each other, while the previous report showed that the latter of the two was much less highly expressed. Both [75] and our study show that tbp3 is more highly expressed during methylotrophic than acetotrophic growth (almost identical fold changes in both studies), and this is supported by the observation that genes in amino acid metabolism and methylamine metabolism are differentially expressed upon its knockout as seen previously.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our data is consistent with a previous study showing that the primary TATA binding protein (TBP; tbp1 ) transcript was similarly expressed under the three growth conditions [75]; however, it differs for comparisons of accessory TBPs wherein our data suggest that tbp2 and tbp3 are expressed at similar levels to each other, while the previous report showed that the latter of the two was much less highly expressed. Both [75] and our study show that tbp3 is more highly expressed during methylotrophic than acetotrophic growth (almost identical fold changes in both studies), and this is supported by the observation that genes in amino acid metabolism and methylamine metabolism are differentially expressed upon its knockout as seen previously.…”
Section: Discussionsupporting
confidence: 91%
“…Both [75] and our study show that tbp3 is more highly expressed during methylotrophic than acetotrophic growth (almost identical fold changes in both studies), and this is supported by the observation that genes in amino acid metabolism and methylamine metabolism are differentially expressed upon its knockout as seen previously. Discussion of four additional transcription factors can be found in Additional file 1: Section “ Differentially expressed genes ”.…”
Section: Discussionsupporting
confidence: 90%
“…Seven specific pairs of TFB and TBP (out of the 42 possible combinations) were identified by co-immunoprecipitation and ChIP-seq experiments 24,30 . In a few archaeal species such as Methanosarcina , multiple TBP paralogues exist alongside a single TFB paralogue 27 . Without much variation in the TATA-box being possible and no specific TBP–TFB pairs, how might the multiple TBPs in Methanosarcina achieve their role in transcription regulation?…”
Section: Evolution Of Tbp and Tfb/tfiib Multiplicity In Eukaryotes Anmentioning
confidence: 99%
“…In vivo studies have shown that Archaea must retain at least one gene encoding TBP and one gene encoding TFB, although many archaeal species encode multiple TBP and TFB isoforms (6,21,(30)(31)(32)(33)(34)(35). Some differences in promoter sequence preferences and protein pairing have been noted in TBP-TFB isoform pairs (36)(37)(38)(39)(40)(41), but these minor differences are not on par with the clear but not always radical promoter sequence differences noted for alternative factors in bacterial transcription (39,42).…”
Section: Basal Transcription Factorsmentioning
confidence: 99%